The Role of Bumdesa in Efforts to Increase Msme Income for Traditional Snacks - Khusniyah Khusniyah; Dwi Apriyanti Kumalasari; Nia Agus Lestari; Sussanti Sussanti ; Bagus Ramadhani W (UNIVED Press, Dehasen University Bengkulu, 2024)
Purpose: This study aims to determine the role of BUM Desa (village-owned enterprises) in increasing the income of small traditional snack businesses. Methodology: The research was conducted in Kedungsumur Village, Krembung District, Sidoarjo Regency, using a qualitative approach. The study was carried out from January 2023 to April 2023. The research location was selected using a perceptive method with key informants. Informants included all elements related to village governance and MSME actors. Results and Findings: The results indicate that BUM Desa can increase MSME income in traditional snacks by enhancing skills through training. This includes financial management training, product quality improvement training, digital marketing training in collaboration with external parties, and facilitating MSME legal permits. Novelty and Originality: This study provides evidence of BUM Desa’s effectiveness in boosting MSME incomes and community welfare through targeted training and support. Conclusions: The development of BUM Desa enterprises leads to increased MSME income and improved community welfare. Type of Paper: Empirical Research Article